Wrestling shuttle test among weight categories in freestyle wrestlers - Iwai, K.; Yumoto, K.; Takahashi, R.; Nakazato, K. (Applied Physiology, Nutrition, and Metabolism, 2018)
Wrestling weight categories were established by United World Wrestling to conduct wrestling matches in appropriate age and competition categories. A wrestling shuttle test (WST) was developed for estimating wrestling-specific physiological capabilities on the mats.The purpose of this study was to clarify differences of physiological capabilities using the WST among weight categories. Sixty-two male wrestlers participated in this study to measure the WST during a 3 minute period. All the wrestlers were divided into three groups with weight categories for freestyle wrestling in Olympic Games (Light; 57kg, 65kg, Middle; 74kg, 86kg, Heavy; 92kg, 125kg). We found the results of the WST were statistically different among the 3 groups by the ANOVA. The number of repetitions during the WST in the light group was significantly higher than that in the heavy one (Light, 109.8±14.4, Heavy, 97.1±9.1, P<0.05). The present study confirmed the middle group did not demonstrate significant differences compared with the other groups (Middle, 103.5±11.6). Our data also showed the same tendencies in the average speed and distance of the WST. This study suggests that physiological capabilities using the WST are different among weight categories in freestyle wrestlers.